Влияние нестационарности процесса теплопроводности на термическое сопротивление тепловой изоляции - Капинос, Василий Максимович; Пустовалов, Владимир Николаевич; Мезерная, Мария Витальевна (НТУ "ХПИ", 2004)
For the transient conduction predictions the relations which describe convective heat exchange are used in the same form as for the steady-state conduction, which could not be always justified. In this connection the approximate solution of the transient conduction problem for an unlimited plate was considered with the replacement of its thermal resistance by the boundary conditions of the third kind. It is shown that the conventional heat transfer coefficient on the insulated plate in the form of the ratio of.
Keywords: задачи теплопроводности; коэффициент теплопроводности; изолируемая поверхность; слой изоляции; параболический профиль температуры; правило Лейбница